The Effectivity Of Public Services Based On Smart Goverment In Bukit Raya Distric Pekanbaru City - Harapan Tua Ricky Freddy; Willya Achmad; Mimin Sundari Nasution (Universitas Sultan Ageng Tirtayasa, 2022)
The Bukit Raya District in Pekanbaru City is the first sub-district to implement one of the pillars, namely E-Government, from the realization of the Pekanbaru City Vision, also known as the Smart City Madani concept. The Bukit Raya District Government of Pekanbaru City, based on Pekanbaru Mayor Regulation Number 56 of 2019, has made a transformation in the form of various public service innovations by utilizing the use of IT technology to facilitate services as one of the indicators of the pillars of smart government (Smart Government) with the vision of working hard, being disciplined, creative, innovative, and having an entrepreneurial spirit and spirit. This is intended to create clean governance and the realization of good governance in order to provide quality, fast, precise, cheap, and good public services. The research problem that will be answered is how effective the transformation of public services based on Smart Government is applied in Bukit Raya District, Pekanbaru City. The theory used refers to the opinion of Bryson (2002) about hexagonal services, which rests on the assumption that services that are considered effective must go through a market test in the Service Management System. The research method used is qualitative with a case study approach. Relevant analysis methods are performance analysis techniques, individual experiences, and institutional behavior (Moeleong, 2006; Bugin, 2011). The results showed that the effectiveness of the transformation of public services based on